Financing resources available for local economic development - VELICU, Ileana-Cosînzeana (Annals of Spiru Haret University. Economic Series, 2012)
This paper reveals that domestic credit is becoming more involved in local economic development, even if it is considered an expensive resource. The loans are presented as a resource available for various “actors” of the local community – individuals, business agents and local authorities.